DAPT, a γ-Secretase Inhibitor, Suppresses Tumorigenesis, and Progression of Growth Hormone-Producing Adenomas by Targeting Notch Signaling - Feng, Jie; Wang, Jianpeng; Liu, Qian; Li, Jiye; Zhang, Qi; Zhuang, Zhengping; Yao, Xiaohui; Liu, Chunhui; Li, Yangfang; Cao, Lei; Li, Chuzhong; Gong, Lei; et al. (Frontiers in Oncology, 2019)
Advances in the understanding of growth hormone-producing adenomas (GHomas) are ongoing, but current therapy is limited by moderate and variable efficacy and in need of life-long treatment. In this study, the molecular signaling pathway related to GHoma was investigated by proteomics and transcriptomics. The differentially expressed proteins and genes were significantly enriched in Extracellular Matrix-Receptor Interactions, Notch Signaling, Basal Cell Carcinoma Signaling, JAK-STAT3, Wnt Signaling and Glioblastoma Multiforme Signaling by Ingenuity Pathway Analysis. Furthermore, the Notch2/Delta-like canonical Notch ligand (DLL) signaling pathway was identified to be associated with tumorigenesis and invasiveness of GHoma. In 76 patients, Notch2 and DLL3 were upregulated in invasive compared to those in non-invasive GHoma (p<0.05). Disease-free survival was significantly longer in patients with low, compared with high, DLL3 expression (p=0.027). Notch 2 knockdown inhibited cell migration in both GH3 cells and primary GHoma cells, along with downregulation of the mRNA expression of related genes. DAPT, a γ-secretase inhibitor, inhibited tumor growth and invasion in vivo and in vitro and suppressed the release of growth hormone in primary GHoma cells. The involvement of Notch2/DLL3 signaling in GHoma progression warrants additional study of Notch inhibitor, DAPT, as a potential GHoma treatment.